A comparison of two types of sheep grazing management in a forest-grass steppe ecotone in southern Patagonia - Ormaechea, Sebastián Gabriel (2011)
A sustainable silvopastoral production in southern Patagonia ranch is the key for conservatioon of Nothofagus antarctica native forest under grazing management. The goal of this work was to compare the traditional grazing management whith a integral silvopastoral management that included strategic separation in homogenous areas (grass steppe, forest and riparian meadows) and stocking rate adjustment to grassland net primary production in order to increase the production levels of the extensive sheep farms in the forest grass steppe region with a sustainable practice.